2009
DOI: 10.1016/j.antiviral.2008.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Prophylaxis with cationic liposome–DNA complexes protects hamsters from phleboviral disease: Importance of liposomal delivery and CpG motifs

Abstract: Cationic lipid DNA complexes (CLDC) are cationic/neutral lipid carriers complexed with plasmid DNA that when administered systemically results in a robust T H 1 cytokine response. CLDC have been shown to be effective in prophylaxis and therapeutic treatment of animal models of viral disease. To determine the contribution of liposomal delivery and CpG content of the plasmid DNA to the efficacy of CLDC; plasmid, CpG-free plasmid DNA, or CpG-containing oligodeoxynucleotides (ODN) with and without liposomes, as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…PTV infection in humans is generally asymptomatic or limited to a mild febrile illness (Peters and LeDuc, 1984). Small animal and cell culture model systems based on infection with the less biohazardous PTV and RVFV vaccine strain, MP-12, respectively, are often employed to evaluate experimental therapies early in the preclinical development process (Gowen et al, 2009; Gowen et al, 2006a; Gowen et al, 2006b; Gowen et al, 2008b; Gowen et al, 2007a; Gowen et al, 2007b; Sidwell et al, 1988; Smee et al, 1991). Ultimately, advanced studies employing authentic RVFV strains in rodent or nonhuman primate models are required for continued preclinical development (Gowen and Holbrook, 2008; Peters et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…PTV infection in humans is generally asymptomatic or limited to a mild febrile illness (Peters and LeDuc, 1984). Small animal and cell culture model systems based on infection with the less biohazardous PTV and RVFV vaccine strain, MP-12, respectively, are often employed to evaluate experimental therapies early in the preclinical development process (Gowen et al, 2009; Gowen et al, 2006a; Gowen et al, 2006b; Gowen et al, 2008b; Gowen et al, 2007a; Gowen et al, 2007b; Sidwell et al, 1988; Smee et al, 1991). Ultimately, advanced studies employing authentic RVFV strains in rodent or nonhuman primate models are required for continued preclinical development (Gowen and Holbrook, 2008; Peters et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…The eastern Panamanian Adames strain of PTV (PTV-A) causes disease in hamsters and mice similar to that seen in natural RVFV infections, and therefore serves as a safer and more cost effective alternative to study disease pathogenesis (Anderson et al, 1990; Fisher et al, 2003; Gowen et al, 2006a; Perrone et al, 2007; Pifat and Smith, 1987) and pre-clinical antiviral drug development (Gowen et al, 2006b, 2007a, 2007b; 2009; Sidwell et al, 1988b). Though previous studies indicated PTV-A was only able to induce disease in weanling age mice (Pifat and Smith, 1987), recent work in our lab has established PTV-A’s ability to produce lethal disease in 7–8-week-old mice (Gowen et al, 2006a); however, the disease histopathology has not been examined in these older mice.…”
Section: Introductionmentioning
confidence: 99%
“…Basic knowledge, such as the mechanism by which bacterial clearance may be achieved in the host, is expected to contribute to the development of new strategies to improve the control of this disease. Recently, a number of studies have described the development of novel antimicrobial strategies that target the host immune response rather than the pathogen (12)(13)(14). These immunotherapeutics target host pathways that either directly activate effector cells or relieve pathogen-induced suppression of host killing mechanisms, resulting in the control and elimination of a wide variety of microorganisms (14).…”
mentioning
confidence: 99%